EFEKTIVITAS DETEKSI DINI GANGGUAN BAHASA DAN BICARA DI POSYANDU ANYELIR DAN POSYANDU SEKAR ASIH KOTA BANDUNG: Effectiveness of Early Detection of Language and Speech Disorders at the Anyelir and the Sekar Asih Posyandu, Bandung - Yosrika Yosrika (JURNAL TERAS KESEHATAN, 2021)
The growth and development of children under five is very important to be monitored, considering that this period is the golden age period during the child's development. Some children experience developmental delays or disorders. One of the developmental disorders that is often encountered is a delay in speech. Early detection of language and speech disorders will greatly help parents to describe whether their children have speech delays or other disorders. However, many parents do not have sufficient knowledge about language and speech disorders. Based on this condition, this study aims to determine the effectiveness of early detection of language and speech disorders at Anyelir Posyandu and Sekar Asih Posyandu to raise awareness about the importance of early detection for toddlers. This study used a qualitative approach with data collection through the technique of interview, observation, and documentation study. The results of the study show that the level of awareness among parents increases towards the growth and development of their child's language after parents get information about early detection of language and speech disorders. By doing early detection on the problems experienced by their children, parents can get further information and treatment if needed.